Phylogenetic and pathogenic variability of strains of Ralstonia solanacearum causing moko disease in Colombia (2020)
Moko disease, caused by the bacterium Ralstonia solanacearum, is one of the most devastating diseases of Musa spp. in Colombia, where banana and plantain are major crops. The disease epidemiology is poorly understood and little is known about the diversity of the bacterial populations associated with this disease. This study assessed the diversity, phylogenetic relationship and pathogenicity of R. solanacearum strains associated with moko disease in Colombia. For this, the genetic diversity of 65 isolates obtained from four banana/plantain-growing regions was evaluated by using multiplex PCR and analysing the partial sequences of the mutS, rplB and egl genes. These analyses revealed that all the strains belonged to the R. solanacearum phylotype II, sequevars 4 and 6. In addition, the phylogenetic analysis assorted the strains into three subgroups, which matched the region of isolation: (i) central region (i.e. Eastern plains and Andes, IIB/4); (ii) northwest (i.e. Uraba and a few strains from Magdalena, IIB/4); and (iii) north coast (Magdalena and a few strains from Uraba, IIA/6). In addition, this evolutionary pattern was associated with pathogenicity, as 63 of the 65 iso lates caused wilting of banana and plantain plants under greenhouse conditions, whilst only 32, those isolated from the central region, caused such symptoms in tomato plants. In conclusion, this study shows that banana and plantain crops in Colombia foster genetically diverse strains of R. solanacearum that belong to at least three different genetic groups, which show biogeographic and host range association